Meningkatkan Kemampuan Membaca Intensif Dengan Metode Cooperative Integrated Reading Composition Pada Peserta Didik: Improving Teachers' Professional Competence To Develop 2013 Curriculum Teaching Materials Through Workshop At Samba Danum SDN-2 - Sumarsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The objectives of the School Action Research with the title: